Incidence of Mutations in the ALPL, GGPS1, and CYP1A1 Genes in Patients With Atypical Femoral Fractures. (22nd June 2018) - Peris, Pilar; González‐Roca, Eva; Rodríguez‐García, Sebastian C; del Mar López‐Cobo, María; Monegal, Ana; Guañabens, Núria
ABSTRACT: Atypical femoral fractures (AFFs) are uncommon and often related to prolonged bisphosphonate (BP) treatment. Isolated cases have been linked to mutations of tissue nonspecific alkaline phosphatase ( ALPL ). Moreover, mutations in the geranylgeranyl pyrophosphate synthase ( GGPPS ) gene, which can be inhibited by BPs, and in the enzyme of the cytochrome P450 superfamily ( CYP1A1 ), related to the metabolism of several drugs, have also been associated with AFF development. Our aim was to analyze the incidence of ALPL, GGPS1, and CYP1A1 gene mutations in patients with AFFs and their clinical characteristics. Seventeen women with AAFs were included. All patients underwent Sanger sequencing of the ALPL, GGPS1, and CYP1A1 genes, analyzing the presence of mutations and polymorphisms in these genes. The clinical characteristics of the patients, previous treatments, ALP substrates (vitamin B6 and phosphoethanolamine), bone turnover markers, and bone mass were also analyzed. Three of 17 patients (17.6%) presented heterozygous mutations in the ALPL (p.Gly288Ala) or CYP1A1 (p.Arg136His, p.Val409Ile) genes. Only the patient with the ALPL mutation presented increased ALP substrates. Patients with CYP1A1 variants had glucocorticoid‐induced osteoporosis. All patients were previously treated with BPs during 85.5 ± 38 months, and nearly 50% were also treated with glucocorticoids. The AFF was bilateral in 35% of cases. In conclusion, ALPL and CYP1A1 mutations may be related to the development of AFF in patients treated with BPs. The evaluation of ALP substrates in patients with low ALPL levels allows the identification of patients with hypophosphatasia. The role of CYP1A1 mutations in AFF needs further study. © 2018 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.